Polyarenes accumulation in tundra ecosystem influenced by coal industry of Vorkuta - Yakovleva, Evgenia; Gabov, Dmitriy (Polish Polar Research, 2020)
Polycyclic aromatic hydrocarbons (PAHs) are organic compounds characterized by carcinogenic, toxic and mutagenic effect on life organisms. The mining and burning of coal are widely practiced in the tundra zone which results in the release of PAHs. The studies of PAHs content in organogenic horizon of tundra soil and southern tundra plants were performed at the control sites and at areas affected by coal industry. The soil and plants were analyzed for PAHs by HPLC. It was established that tundra soils, lichens and mosses are contaminated with polyarenes to a larger extent in the areas affected by the coal mining. The peak of PAHs concentration in the area affected by the Vorkutinskaya coal mine was observed within the distance of 0.5 km, and within 1.0 km in the area affected by the thermal power station. We propose to use diagnostic correlations of fluoranthene/ chrysene and fluoranthene/benz[b]fluoranthene in soils and mosses Pleurozium schreberi (Brid.) Mitt. to characterize the origin of polyarenes in tundra ecosystems. The similar polyarenes distribution is found in the soils and plants under the influence of coal industry. With polyarenes supply from industrial sources decreasing, their bioaccumulation level in the plants is reduced. We recommend Pleurozium schreberi to be used as a pollution indicator of tundra phytocenoses with PAHs and leaves of Betula nana L. for assessment of short-time changes of polyarene contents. The general contents rather than the surface accumulations are more suitable for the monitoring studies.